2018
DOI: 10.1155/2018/3510979
|View full text |Cite
|
Sign up to set email alerts
|

Study on Structural Service Performance of Heavy-Haul Railway Tunnel with Voided Base

Abstract: The structural design of heavy-haul railway tunnels still follows the design method of ordinary railway tunnels. Most of them do not take into account the influence of large axle load of 30 t or more, let alone such problems as void of surrounding rock under long-term dynamic loads. In order to analyze the dynamic response of heavy-haul railway tunnels under long-term reciprocating cyclic dynamic loads, considering the factors such as axle load of vehicle body, unsprung mass, and track irregularity, the vibrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…It is visible that there are no relevant track defects and the longitudinal level records remain within the threshold values of the alert limits for D1 and D2, which indicates an overall good geometric quality of the track. It is also interesting to note that the locations denoting disturbances in the longitudinal level records of D1 do not match those of D2, which is expected given that the track defects of these two wavelength ranges normally have different sources [2,[29][30][31].…”
Section: Description Of the Case Studymentioning
confidence: 99%
“…It is visible that there are no relevant track defects and the longitudinal level records remain within the threshold values of the alert limits for D1 and D2, which indicates an overall good geometric quality of the track. It is also interesting to note that the locations denoting disturbances in the longitudinal level records of D1 do not match those of D2, which is expected given that the track defects of these two wavelength ranges normally have different sources [2,[29][30][31].…”
Section: Description Of the Case Studymentioning
confidence: 99%
“…Based on a fatigue test, Liu et al [12] also found that the lower the stiffness of the basement, the faster the development of the fatigue damage of tunnel inverted arches. Zhang et al [13] stated that when a void exists in the base, the displacement and maximum principal stress of the tunnel bottom structure caused by train load increase significantly; then, based on the existing S-N curve of concrete tension fatigue, the calculation suggested that the fatigue life of the tunnel bottom structure is less than 100 years when the basal void is ≥2 m.…”
Section: Introductionmentioning
confidence: 99%